P 64 Evaluation of cortical reorganization in patients with facial palsy by navigated transcranial magnetic stimulation (nTMS) and functional MRI. (May 2022) - Zdunczyk, A.; Denker, M.; Engelhardt, M.; Picht, T.; Dengler, N.; Vajkoczy, P.
Abstract : Background: Bell's palsy develops due to a lesion of the facial nerve and might occur idiopathic, as a result of masses in the cerebello-pontine angle or brainstem or as a result of trauma or surgery. This prospective study aims to evaluate cortical reorganization after facial nerve palsy by means of navigated transcranial magnetic stimulation (nTMS), diffusion tensor imaging (DTI) and resting state functional magnetic resonance imaging (rsfMRI). Methods: The study is based on a prospective patient and healthy subject cohort study. The patient group consist mainly of patients with tumors of the cerebello pontine angle suffering from a postoperative facial nerve palsy. The House & Brackmann scale, and Sunnybrook scale were used to assess the facial nerve function. The cortical excitability of the facial network was determined by navigated transcranial magnetic stimulation (nTMS) with the following parameters: Resting motor threshold (RMT), Recruitment curve (RC), Cortical silent period (CSP) and Motor area. By means of functional and diffusion MRI corticobulbar tract integrity and interhemispheric connectivity were displayed. Results: We present the first results of our ongoing trial. In these two patients we were able to detect a reduced cortical excitability expressed by an increased RMT interhemispheric ration (1, 3; 0, 6). The facial motor area of the affected hemisphere was reduced in size (218 mm2 vs. 355, 1 mm2) and there was a diminished interhemispheric connectivity (pFWE (corr) = 0.03) Conclusion: By better characterization of neuronal recovery, risk groups of patients without clinical improvement can be defined early. This gives this group a better chance to receive early surgical facial nerve reconstruction, therefore resulting in a better functional outcome. Furthermore, evaluation of cortical excitability and representation of the facial motor network after surgery might also display postoperative recovery.